Sociopedagogical Transformation of Coastal Communities: Integration of Education in the Vortex of Social Change and Development of Patimban International Port - Agus Maksum; Ade Jamarudin; Ofa Ch Pudin; Fatimatuzzahro (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The construction of Patimban International Port in Subang Regency has triggered a fundamental social transformation for coastal communities. This study aims to analyze the role of education as an instrument for adaptation and mitigation of marginalization amidst the conversion of maritime land into industrial areas. Using descriptive qualitative methods, the study explores the synergy between religious education (MDTA) and vocational training in maintaining a balance between modernity and local identity. The findings indicate that structured educational interventions are crucial in transforming the community profile from a traditional agrarian to a competent industrial workforce. Educated youth groups are found to have a strategic role as agents of change, facilitating communication between local values ​​and global demands. The integration of the educational dimension into national development planning is a determining factor for the social sustainability of coastal communities.